A basement culmination in the Scandinavian Caledonides formed by antiformal stacking (Bångonåive, northern Sweden) - Greiling, Reinhard O.; Gayer, Rodney A.; Stephens, Michael B. (Geological magazine, 1993)
The Bångonåive basement culmination, a doubly plunging antiform trending SW-NE in its southern part and SSW-NNE in the north, is part of a major Caledonian antiform in north-central Scandinavia. Crystalline, Proterozoic basement rocks (mainly syenite) are unconformably overlain by a sedimentary cover including tillites at the base, passing up into arkoses, quartzites and shales, capped by black phyllites. This sequence is correlated with the Varangian to Cambrian succession of the Baltoscandian platform farther east. Detailed mapping revealed a succession of five basement-cover horses, which represent the accessible part of an antiformal stack exposed beneath the Middle and Upper Allochthons and taken here as the Lower Allochthon structural level.Caledonian deformation varies in intensity from penetrative near thrusts and in pelitic rocks to very weak in the more internal parts of the horses. A penetrative foliation is associated with the growth of white mica and rare biotite. This early fabric is overprinted by a mylonitic foliation related to localized shear zones, which separate the structural units within the Lower Allochthon. Stretching and mineral lineations trend WNW-ESE and related shear-sense criteria indicate transport (top) towards the ESE. Structural units (horses) are thrust into an antiformal stack and folded around the lowermost horse exposed, which is itself folded into an anticlinal lift-off fold. Towards the northeast, the antiformal stack is overprinted by a pop-up and an out-of-sequence thrust. The latter breached the roof of the Lower Allochthon and transported part of it over the Middle and Upper Allochthons. Further folds are associated with lateral and oblique ramps in the Lower Allochthon. These structures relate very well with the complex fold pattern previously observed in the higher structural units and thrust tectonics provides a straightforward genetic explanation for these folds. Therefore, earlier genetic models of the Bångonåive basement culmination as a simple imbrication of basement into higher units, as a buckling structure or as a gravitational dome structure are rejected here. The structural information, supported by gravimetric data, is consistent with an essentially flat regional detachment surface (2° dip) extending from the present external Caledonian margin to the base of the Bångonåive antiformal stack.